Learning to talk about movement through time and space: the development of narrative abilities in spanish and english - Slobin, Dan I.; Bocaz, Aura (Lenguas Modernas, 2017)
Narratives were gathered from Spanish- and English-speaking children and adults in response to a pictured story. Child subjects ranged in age from 3 to 11. Comparable samples were gathered in Spain, Chile, Argentina, and the United States. The data were analyzed in terms of the acquisition of grammatical means for expressing aspect, processes and states, event phases, and motion. It was found that children acquiring Spanish in all three countries quickly mastered the range of verbal aspectual inflections. Spanish grammar seems to orient children towards conceptions of the boundedness and extensión of events in time. Differences between the verbal systems of Spanish and English seem to lead Spanish-speaking children to be more explicit about states and English-speaking children to be more explicit about processes and movements through space. In all four countries, school age children learn to flexibly use grammatical devices in the construction of coherent narrative. It is suggested that, in acquiring a mother tongue, one adopts a particular sort of verbalized orientation to experience, as embodied in the set of grammatical options provided by the language.